S46 Evaluation of phosphorylated 70s6k expression in malignant pleural mesothelioma and its association with patient survival. (12th November 2019) - Tariq, S; Oguh, L; Campbell, A; Cawkwell, L; Lind, MJ
Abstract : Introduction and objective: Dysregulation of Mammalian target of rapamycin pathway has been shown in various cancers. Phosphorylated 70S6k is a vital downstream signalling protein of this pathway, dysregulation of this protein has also been linked to various malignancies and potentially to patient survival. In this study, we aimed to investigate the expression of phosphorylated 70S6K in MPM and evaluate its relationship with patient survival. Methods: We performed immunohistochemical analysis on archival MPM tissue samples to examine the expression of phosphorylated 70S6K. Western blot analysis was also performed to evaluate the expression this protein in MPM cell lines. Histopathological and clinical data of relevant patients were obtained from Hull Royal Infirmary. Univariate analysis was performed for protein expression using Kaplan Meier survival curves with log rank analysis. Multivariate Cox regression analysis taking histological subtypes into account was performed, to assess the effect of phosphorylated 70S6K expression on patient survival. Results: Our cohort consisted of total 79 archival MPM samples which included 43 Epithelioid, 24 Biphasic, and 12 Sarcomatoid MPM tissue samples. Of these 79 samples, 45 (57%) were found to be negative for Phospho 70s6K expression while 34 (43.%) showed positive expression. A significant difference in expression of phospho 70s6K was found between MPM subtypes, on immunohistochemistry (p=0.01). Phospho 70S6K protein was expressed in MSTO-211H and A549 cells, very weak expression in the NCI-H2452 cells was detected but none in the NCI-H2052 cell. No significant difference in survival was found between patients who had positive and negative phospho 70s6K expression (p=>0.05). Conclusion: Our data suggest that phosphorylated 70S6K is expressed in MPM and there was a difference in expression of phospho 70s6K between MPM subtypes. No statistically significant association was found between phosphorylated 70S6K expression and patient prognosis.